WAYS TO TEACH ADOLESCENTS SELF-AWARENESS AND SELF-MANAGEMENT IN THE PROCESS OF EXTRACURRICULAR EDUCATION - Imomova Manzura Ibodullaevna (Galaxy International Interdisciplinary Research Journal, 2021)
Successful work on oneself in the process of extracurricular education, first of all, understanding oneself, one's strengths and weaknesses, understanding one's position, place and importance in the community, being able to determine one's future independently, or implies a certain level of self-awareness.